Hydrodynamic evaluation of a filter bed of porous material from stratified sedimentary rocks for the removal of turbidity in surface waters - Angel Villabona-Ortíz (Elsevier, 2022)
In this study, the behavior of a filter bed of stratified sedimentary rocks was evaluated through the analysis of turbidity removal efficiency and head losses. Two types of sands were used as materials, fine and medium, as well as crushed limestone. The materials were characterized to determine the average particle diameter, porosity, and permeability coefficient, obtaining respectively 0.17 mm, 0.39, and 1 × 10−3 cm/s for fine sand, 0.33 mm, 0.41, and 3 × 10−3 cm/s for medium sand, and 1.26 mm, 0.45, and 1 × 10−2 cm/s for crushed limestone. Hydrodynamic analyses of the clean filter under conditions of rapid filtration were carried out, by which the different rates of filtration to be used in each experiment were determined, establishing a direct correlation between the rate of filtration and the thickness of the bed; in this way, it was possible to determine the maximum bed thickness that could be used to maintain a rate of rapid filtration higher than 120 m/day. A hydrodynamic study with synthetic turbid water prepared at 8 NTU using tap water and bentonite was also carried out. Total head losses and turbidity removal were studied for each material at a rate of 153 m/day with removal efficiencies of 93.7% for medium sand with a loss of 23 cm and 67.8% for limestone with a loss of 4.5 cm and a rate of 389 m/day. It is recommended to use the medium sand and limestone type material for use in surface water filtration processes.